Strategi Manajemen Kepemimpinan Kepala Desa Melalui Pendampingan Berkelanjutan Peran SDGs Desa Dalam Peningkatan Pemberdayaan Tipologi Desa di Kawasan Pesisir - Novianty Djafri; Apriyanto A. J Pauweni; Syamsu Qamar Badu (Jurnal SOLMA, 2021)
Background: Regional development is an issue and problem that is always interesting to study in the design and strategy of sustainable development, including human development, echoed in the concept of the Millennium Development Goals or known as the MDGs, the COVID-19 pandemic period disturbed the situation from various aspects of life in the region. A special area in Sukadamai village, precisely in the coastal zone. This service aims at Sustainable Assistance through Management of the Utilization of Village SDGs in Empowering Increasing Economic Income of MSME Groups in Coastal Areas. Method: Method with lectures, discussions and hands-on practice conducted jointly by students, along with target groups, communities and government (stakeholders). Results: Empowerment of the synergy of Increasing Economic Income with villages without poverty through MSME groups in coastal areas; as well as finding the leadership management model for the Creative Village Head; MSMEs/Entrepreneurship Based on SDGs. Conclusion: Getting a creative leadership model to improve the Village Head Leadership Management Strategy so that the Sustainable Assistance of the SDGs Role of Bilato Village can increase the Empowerment of Village Typology in the Coastal Area of ​​Bilato Village, Bilato District, Gorontalo Regency.